Isolated and Complex Scimitar Vein Anomalies and Their Differentiation from the Meandering Right Pulmonary Vein - Lee, Meng-Luen (Yonsei University College of Medicine, 2007)
PURPOSE: Four pediatric patients with isolated (the adult form) and complex (the infantile form) scimitar vein anomalies were reviewed and compared with patients with meandering right pulmonary veins. MATERIALS AND METHODS: From January 1990 to December 2006, 4 female patients, aged 2 days to 3.5 years, with isolated and complex scimitar vein anomalies were retrospectively studied. The clinical features, chest radiographs, echocardiography, magnetic resonance imaging, magnetic resonance angiography, computer tomography, bronchography, cardiac catheterization with angiography, surgery, and autopsy were reviewed to substantiate the diagnosis of isolated and complex scimitar vein anomalies. RESULTS: Clinical manifestations were lung infections with radiographic scimitar signs in 4 patients (3 right; 1 left), respiratory distress, congestive heart failure, pulmonary hypertension and/or cyanosis in 3 patients, dextrocardia, heterotaxy, and/or right atrial isomerism in 2 patients, as well as dextroversion, right bronchial isomerism, bronchial stenosis, and/or sepsis in 1 patient. Two patients with right atrial isomerism expired. CONCLUSION: The clinical discrimination between scimitar vein anomaly with and without cardiovascular and bronchopulmonary malformations is crucial for the outcomes vary.